Dune - Herbert, Frank; Gaiman, Neil (New York : Penguin Books, 2016)
"Science fiction's supreme masterpiece, Dune will be forever considered a triumph of the imagination. Set on the desert planet Arrakis, it is the story of the boy Paul Atreides, who will become the mysterious man known as Muad'Dib. Paul's noble family is named stewards of Arrakis, whose sands are the only source of a powerful drug called "the spice." After his family is brought down in a traitorous plot, Paul must go undercover to seek revenge, and to bring to fruition humankind's most ancient and unattainable dream. A stunning blend of adventure and mysticism, environmentalism and politics, Dune won the first Nebula Award, shared the Hugo Award, and formed the basis of what is undoubtedly the grandest epic in science fiction. "--
HB
Keywords: FICTION / Science Fiction / High Tech; FICTION / Classics; FICTION / Literary; Science fiction